Toward a Qur’anic Theory of Mindfulness: Integrating Consciousness, Spirituality, and Emotional Regulation in Tafsīr al-Kabīr and Tafsir al-Azhar - Zakiyah, Ermita; Abdul Kadir Riyadi; Ghozi, Ghozi; Wardatun Nadhiroh (Journal of Ushuluddin and Islamic Thought, 2025)
Contemporary mindfulness research has been dominated by secular psychological paradigms, leaving the Qur’anic conception of consciousness insufficiently theorized. This article seeks to develop a Qur’anic mindfulness construct by integrating insights from classical and modern Qur’anic exegesis and examining its relationship with David R. Hawkins’ map of consciousness. Employing qualitative library research, the study analyzes two influential commentaries: Tafsīr al-Kabīr of Fakhr al-Dīn al-Rāzī and Tafsir al-Azhar of Hamka. The findings demonstrate that Qur’anic mindfulness constitutes a psychospiritual model of consciousness grounded in divine awareness, emotional regulation, and moral transformation. The construct operates through interconnected mechanisms of dhikr, reflective self-awareness, tawakkul, tazkiyat al-nafs, and patient engagement with emotional experiences. While Hawkins’ framework helps illuminate gradations of consciousness, the Qur’anic model extends beyond psychological states by incorporating transcendental orientation and ethical accountability. Furthermore, the study identifies two complementary exegetical approaches: al-Rāzī develops an epistemological and text-centered formulation of consciousness, whereas Hamka emphasizes its contextual and practical dimensions. The article contributes to the growing field of Islamic psychology by proposing a theoretically grounded model of Qur’anic mindfulness that may serve as a foundation for future psychospiritual intervention studies.